2017
DOI: 10.1177/1751143717700166
|View full text |Cite
|
Sign up to set email alerts
|

Basic critical care echocardiography: How many studies equate to competence? A pilot study using high fidelity echocardiography simulation

Abstract: Background: Assessment of competence in basic critical care echocardiography is complex. Competence relies on not only imaging accuracy but also interpretation and appropriate management decisions. The experience to achieve these skills, real-time, is likely more than required for imaging accuracy alone. We aimed to assess the feasibility of using simulation to assess number of studies required to attain competence in basic critical care echocardiography. Methods: This is a prospective pilot study recruiting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Our previous studies demonstrated the relationship of deviation angle to competence level by comparing the scores of experts vs. trained novices and of untrained vs. trained novices (Sheehan et al, 2013;Skinner et al, 2016). Others have also reported that simulator-based measurement of psychomotor skill reflects provider experience (Bowcock et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous studies demonstrated the relationship of deviation angle to competence level by comparing the scores of experts vs. trained novices and of untrained vs. trained novices (Sheehan et al, 2013;Skinner et al, 2016). Others have also reported that simulator-based measurement of psychomotor skill reflects provider experience (Bowcock et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Post-workshop supervised practice was significantly hampered by scheduling difficulties between novices and trainers, all of whom had clinical care responsibilities. Nevertheless, the ideal number of practice scans necessary to achieve competency in FoCUS is still a matter of contention [ 22 ]. While the 2018 EACVI consensus document recommends a minimum of 50 practice scans [ 9 ], the FATE curriculum that we followed recommends 20, ten of which must be supervised.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in the development of alternative methods such as objective structured assessments, including the use of simulators. Despite the development of such assessments, they have yet to be widely adopted [52][53][54].…”
Section: Echocardiographymentioning
confidence: 99%
“…High-fidelity simulators have been proven to be valid and reliable in a number of examination settings, including ultrasound and in particular, a validated TUS simulator test has been recently developed. The final assessment of "does" is likely best measured using either portfolios with ongoing summative and formative assessments or logbooks with supervision; however, minimum numbers of procedures or scans not only remain undefined but may not be a valuable metric given the uncertainty around the validity and the variations in learning curves [31,33,39,41,43,54,58].…”
Section: Basic-level Tus Operatormentioning
confidence: 99%